Teaching literature in times of crisis - Ahlberg, Sofia 1973- (Routledge, an imprint of the Taylor & Francis Group, 2021)
"Teaching Literature in Times of Crisis introduces teachers to methods for reading and studying literature with the aim of strengthening and promoting resilience and resourcefulness in and out of the literature classroom to empower students as global citizens with local roles to play."